2019
DOI: 10.1128/jcm.00204-19
|View full text |Cite
|
Sign up to set email alerts
|

Utility of DNA Next-Generation Sequencing and Expanded Quantitative Urine Culture in Diagnosis and Management of Chronic or Persistent Lower Urinary Tract Symptoms

Abstract: Many patients suffer from chronic, irritative lower urinary tract symptoms (LUTS). The evaluation and management of these patients have proven difficult with the use of standard diagnostic tools, including urinalysis and urine culture. The growing body of literature on the urinary microbiome has looked at the possible implications of the bladder microbiome and dysbiosis, or perturbations in the microbiome, in conditions associated with chronic LUTS. Disorders such as recurrent urinary tract infections (UTIs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 31 publications
0
50
0
Order By: Relevance
“…Taken together, acute uncomplicated cystitis can be regarded as a temporary infection caused by a specific causative organism, but in recurrent cystitis, dysbiosis seems to play a more important role in the pathophysiology [ 41 ]. In addition, even within the same recurrent group, there is a possibility that the dysbiosis changes as the condition is prolonged.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, acute uncomplicated cystitis can be regarded as a temporary infection caused by a specific causative organism, but in recurrent cystitis, dysbiosis seems to play a more important role in the pathophysiology [ 41 ]. In addition, even within the same recurrent group, there is a possibility that the dysbiosis changes as the condition is prolonged.…”
Section: Discussionmentioning
confidence: 99%
“…This theory was later called into question by the initiation of the National Institutes of Health sponsored Human microbiome project which demonstrated the presence of a bladder and urinary microbiome [ 56 ]. While the data surrounding the urinary microbiome is still in its infancy, existing work has shown the primary occupants to include organisms from the genera Lactobacillus , Garderella , Streptococcus , Staphylococcus and Corynebacterium [ 58 ].…”
Section: Next Generation Sequencing (Ngs)mentioning
confidence: 99%
“…When a sample of urine is tested using NGS, the output reports bacterial presence in terms of relative sequence reads amongst species instead of absolute values [ 60 ]. To date, MicroGen DX and Aperiomics are two companies which offer NGS as a clinical application for the diagnosis of UTI’s [ 58 ].…”
Section: Next Generation Sequencing (Ngs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Pervasive implementation of techniques designed to identify all microorganisms in the urine, most notably sequencing-based techniques (e.g., 16S rRNA sequencing or whole genome sequencing), but also cultivation-based methods of expanded quantitative urine culture [ 13 , 63 ], has shown that a wide range of bacterial species can be found in the urine of healthy, asymptomatic individuals [ 64 , 65 ]. The analysis of the urinary microbiome as a field of research is still in its infancy; hence, there is much to learn and discover regarding its role in maintaining urinary bladder and urinary tract homeostasis in different contexts.…”
Section: The Increasingly Appreciated Significance Of the Urinary mentioning
confidence: 99%